The eye opener: Preparing for and performing facility siting to best communicate with upper management. Issue 2 (17th July 2016) - James, Michael
Abstract : Upon completion of a facility siting study, a major step in the critical path for implementation is acceptance from upper management on the remediation plan. Communicating with upper management occurs at the end of several steps which can be strategically mapped in order to maximize upper management's understanding of the needs of a site's remediation requirements. Using an example chemical plant, this paper will detail the process of initiating a facility siting study, provide a novel approach to prioritizing building remediation requirements, and discuss how the resulting information can best be framed and communicated to upper management. In addition to discussing strategies for effective communication with upper management on proposed facility siting strategies, the paper also details an online system that could be used for keeping facility siting data evergreen after the study is completed. © 2016 American Institute of Chemical Engineers Process Saf Prog 36: 158–164, 2017